Framing in News Coverage of the Israel–Palestine Ceasefire by Arab Media: An Analysis Based on Robert Entman’s Model - Nazifatul Mardiah; Abdul Basid (Universitas Islam Negeri Palopo, 2025)
Media reporting on the Israel–Palestine ceasefire negotiations often reflects ideological and geopolitical orientations that shape how the conflict is understood by the public. This study investigates how four major Arab-language news outlets—Al Jazeera, Okaz, Sky News Arabia, and BBC News Arabic—construct their framing of the ceasefire agreement between Hamas and Israel. Specifically, the research addresses two questions: (1) how each outlet employs Robert N. Entman’s four framing elements, and (2) what similarities and differences emerge from the comparative framing across these media. Using a descriptive qualitative design, the study analyzes four online articles published during the negotiation stalemate in early 2025. Data were collected through documentation and examined using Entman’s framing devices: problem definition, causal interpretation, moral evaluation, and treatment recommendation. The findings reveal contrasting patterns: Al Jazeera and BBC News Arabic frame Israel as obstructing the ceasefire and emphasize humanitarian impacts; Okaz portrays Hamas as the primary barrier and legitimizes Israel’s security-oriented stance; and Sky News Arabia adopts a more balanced yet moderately pro-Palestinian framing. These variations demonstrate how geopolitical context influences media narratives. The study contributes to conflict communication research by illustrating divergent Arab media framings and underscores the need for critical media literacy in interpreting politically charged news.